Nilotinib in combination with carboplatin and paclitaxel is a candidate for ovarian cancer treatment - Weigel, Marion T.; Rath, Katrin; Alkatout, Ibrahim; Wenners, Antonia S.; Schem, Christian; Maass, Nicolai; Jonat, Walter; Mundhenke, Christoph (Oncology, 2014)
Purpose: Nilotinib is a selective tyrosine kinase inhibitor of c-Kit, Abl and platelet-derived growth factor receptor-α/β. To evaluate nilotinib's potential use as a treatment of human ovarian cancer, we tested nilotinib's preclinical activity in ovarian cancer cell lines with different tyrosine kinase expression patterns. Methods: The effects of nilotinib on ovarian cancer cell growth were studied alone and in combination with carboplatin and paclitaxel. Proapoptotic and antimigratory effects were examined using TUNEL and migration assays. Results: Nilotinib alone and in combination with carboplatin and paclitaxel significantly inhibited cell growth in PDGFR-α-positive ovarian cancer cell lines. The combination of nilotinib with carboplatin and paclitaxel showed synergistic effects on cell proliferation. Nilotinib treatment led to the inhibition of cell migration alone and in combination with carboplatin and paclitaxel. Apoptosis induction occurred in response to nilotinib that increased in combination with carboplatin. Conclusions: Nilotinib may be a feasible targeted therapy option for the treatment of ovarian cancer.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Cell growth; Ovarian cancer; Platelet-derived growth factor receptor; Tyrosine kinase inhibitor